School Health Business Management (Uks) To Improve Healthy Lifestyles In Sd Negeri Dki Jakarta - Christine Hutagalung, Cynthia; Trisnamansyah, Sutaryat; Sulastini, Rita; Handayani, Sri (CV. Inara, 2022)
School Health Business Management (UKS) to improve a healthy lifestyle at SDN Jakarta, has not run optimally in its implementation, so that many UKS programs have not been realized as they should. If there is no solution, it is feared that UKS activities will not run. The specific purpose of this study is to get an overview of UKS management in improving a healthy lifestyle at SDN Jakarta. The general objectives are: a. To find out the UKS management plan in improving a healthy lifestyle at SDN Jakarta, b. To find out the organization of UKS management in improving a healthy lifestyle at SDN Jakarta, c. To find out the implementation of UKS management in improving a healthy lifestyle at SDN Jakarta, d. To find out the assessment of UKS management in improving a healthy lifestyle at SDN Jakarta. e. To find out the problems of UKS management in improving a healthy lifestyle at SDN Jakarta f. To find out UKS management solutions to improve a healthy lifestyle at SDN Jakarta. The philosophical basis of this research is the philosophy of constructivism, while the theoretical basis used is the management theory by GR Terry (2009), the theory by UKS Notoatmodjo, et al (2012) and the theory of healthy lifestyles by Kus Irianto (2004). qualitative. Data collection is done through: Documentation studies, observations, interviews, and triangulation. The results of the research include: planning, organizing, implementing, assessing, problems and solutions for UKS management to improve a healthy lifestyle at SDN Jakarta, requires visionary leadership, responsibility, and upgrading human resources with all supporting facilities so as to produce graduates who care about healthy lifestyles, healthy lifestyles, both in terms of input, process, output and outcome. Conclusion; UKS management to improve healthy lifestyles for SD Negeri DKI Jakarta students which has a positive impact on increasing healthy living behaviors both at school and in their environment